(а-1)x^2+(a+4)x-(a+3)=0 A = a - 1 B = a + 4 C = -(a + 3) 1) А = 0 => 1 корень 2)A не равно 0 => а не равно 1 1) В = 0 => a = -4 -5x^2 + 2 = 0 x^2 = 2/5 2 различных корня 2) С = 0 => a = -3 -4x^2 + x = 0 x(1 - 4x) = 0 2 различных корня 3) В не равно 0 => а не равно -4 С не равно 0=> а не равно -3 (а-1)x^2+(a+4)x-(a+3)=0 D = (a+4)^2 + 4(a-1)(a+3) = a^2 + 8a + 16 + 4a^2 + 8a - 3 = 5a^2 + 16a + 13 >0 D1 = 64 - 260 < 0 => нет таких а ответ: при а = -4 => 2 корня при а = -3 => 2 корня
ответ:1) (5а+3)+(-3а-4)=5а+3-3а-4=2а-1
(5а+ 3)-(-3а-4)=5а+3+3а+4=8а+7
2) (7х2+3х)+(-2х-1)=7х2+3х-2х-1=7х2+ 1х-1
(7х2+3х)-(-2х-1)= 7х2+3х+2х+1=7х2+ 5х+1
3)( 8b2 + 2b - 4)+( 5 - 3b - 9b2)= 8b2 + 2b – 4+5 - 3b - 9b2=-b2-b+1
( 8b2 + 2b - 4)-( 5 - 3b - 9b2)= 8b2 + 2b – 4 -5+3b+9b2=17b2+ 5b-9
4) (11y - 12 - y3)+( 14 - 12y + y3)= 11y - 12 - y3+14 - 12y + y3=-y+y3+2
(11y - 12 - y3)-( 14 - 12y + y3)= 11y - 12 - y3-14+12y-y3=23y-2y3-26
5) (6 + mn + 2)+( 4 - mn - m2)= 6 + mn + 2+4 - mn - m2=12-mn-m2
(6 + mn + 2)-( 4 - mn - m2)= 6 + mn + 2-4+mn+m2=4+2mn+m2
Объяснение:
не благодарите